Cycle of Poems “Aleshkin’s Thoughts” by R.I. Rozhdestvensky: Development of the Traditions of the Genres of Children’s Folklore (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-3-131-143In the third decade of the twenty-first century, the bundle of poetic energy left by talented poets as a legacy to the generation of Russian people who stepped into the world of high technologies does not allow them to sleep peacefully. This is evidenced by the endless stream of films and programs about people who managed to melt the block of totalitarianism. We are talking about the poets of the sixties, including R. I. Rozhdestvensky. His work for more than sixty years excites the reader: lyrics (landscape, love, philosophical, civil, confessional) and poems (“Requiem”, “Dedication”, “Before you Come”, “Waiting”, etc.). This article analyzes the cycle of poems “Aleshkin’s Thoughts” by R. I. Rozhdestvensky, which reflects the artistic world of childhood and has autobiographical features. The poet’s childhood associations were embedded in the poems-monologues of the three-yearold lyric character. The influence of children’s folklore on the structure and content of the cycle is traced. The development of genres of children’s folklore (fairy tales, jokes, nursery rhymes, tall tales, shifters, parodies, witticisms, horror stories, teasers, mimicry, mockingbirds, jokes, excuses, etc.) in the poems “Aleshkin’s thoughts” is revealed. It is noted that the continuation of the development of genres of children’s folklore in the work helped to reflect the serious-laughing perception of the author of the cycle on the life events of the baby.Key words: Rozhdestvensky, poems cycle, childhood world, genre, children’s folklore, development, tradition.